Sustainable healthcare architecture - Guenther, Robin; Vittori, Gail
Written by a leading healthcare architect named one of Fast Company's 100 most creative people in business and a sustainability expert recognized by Time magazine as a Green Innovator, Sustainable Healthcare Architecture, Second Edition is fully updated to incorporate the latest sustainable design approaches and information as applied to hospitals and other healthcare facilities. It is the essential guide for architects, interior designers, engineers, healthcare professionals, and administrators who want to create healthy environments for healing. Special features of this edition include: 55 new project case studies, including comparisons of key sustainability indicators for general and specialty hospitals, sub-acute and ambulatory care facilities, and mixed-use buildings New and updated guest contributor essays spanning a range of health-focused sustainable design topics Evolving research on the value proposition for sustainable healthcare buildings Profiles of five leading healthcare systems and their unique sustainability journeys, including the UK National Health Service, Kaiser Permanente, Partners HealthCare, Providence Health & Services, and Gundersen Health System Focus on the intersection of healthcare, resilience, and a health promotion imperative in the face of extreme weather events Comparison of healthcare facility-focused green building rating systems from around the world Sustainable Healthcare Architecture, Second Edition is an indispensable resource for anyone interested in the design, construction, and operation of state-of-the-art sustainable healthcare facilities.